Human resource management contribution to innovation in small and medium‐sized enterprises: A mixed methods approach. (6th December 2017) - Curado, Carla
Abstract : This article addresses the contribution of human resource management systems (HRMS) and three social resources (trust, knowledge sharing and organizational commitment) to innovation in small and medium‐sized enterprises (SMEs). The study adopts a mixed methods approach by combining quantitative and qualitative methods. Results show that causal configurations leading to innovation in SME are fewer (4) than causal configurations leading to the absence of innovation (6). However, pathways to innovation in SMEs are less demanding than trails leading to the absence of innovation; such results should encourage managers. Results seem to suggest that diminished levels of trust, as well as poor knowledge sharing among individuals, and the existence of normative commitment may prevent innovation, which should alert SME managers. Implications for theory regard the hierarchy of determinants leading to innovation: HRMS beat commitment. Empirical consequences arise: managers aiming to innovate should pay close attention to the implementation of HRMS.